Potential Therapeutic Role of HDAC Inhibitors in FUS-ALS - Tejido, Clara; Pakravan, Donya; Bosch, Ludo Van Den (Frontiers in Molecular Neuroscience, 2021)
Abstract Mutations in the FUS gene cause amyotrophic lateral sclerosis (ALS-FUS). However, the exact pathogenic mechanism of mutant FUS is not completely understood. FUS is an RNA binding protein (RBP) localized predominantly nuclear, but ALS-linked FUS mutations can affect its nuclear localisation signal impairing its import into the nucleus. This mislocalization to the cytoplasm facilitates FUS aggregation in cytoplasmic inclusions. Therapies targeting post translational modifications are rising as new treatments for ALS, and especially acetylation could have a role in the dynamics of RBPs. Research using histone deacetylase (HDAC) inhibitors in FUS-ALS models showed that HDACs can influence cytoplasmic FUS localization. Inhibition of HDACs could promote acetylation of the FUS RNA binding domain (RRM) and altering its RNA interactions resulting in FUS maintenance in the nucleus. In addition, acetylation of FUS RRMs might also favor or disfavor its incorporation in pathological inclusions. In this review, we summarize and discuss the evidence for a potential role of HDACs in the context of FUS-ALS and we propose a new hypothesis based on this overview.